2020
DOI: 10.7759/cureus.7949
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder and Suicidal Risk in Major Depression: Analysis of 141,530 Adolescent Hospitalizations

Abstract: We conducted a cross-sectional study to understand the differences in demographics and psychiatric comorbidities in adolescents with major depressive disorder (MDD) and assess the risk of suicidality due to comorbid attention-deficit/hyperactivity disorder (ADHD). Methods We included 141,530 adolescents (age, 12 to 18 years) with a primary diagnosis of MDD from the nationwide inpatient sample (NIS, 2012-2014), and grouped by a comorbid diagnosis of ADHD (N = 22,665, 16%). Logistic regression analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…Past studies have found adolescents with psychiatric comorbidities like depressive disorders and attentiondeficit/hyperactivity disorder were at a higher risk of SUD, which can lead to impairment of overall functioning [12,13]. Our study focuses on identifying the demographic predictors of suicidal behaviors and assessing the relationship between the spectrum of SUD and suicidal behaviors in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have found adolescents with psychiatric comorbidities like depressive disorders and attentiondeficit/hyperactivity disorder were at a higher risk of SUD, which can lead to impairment of overall functioning [12,13]. Our study focuses on identifying the demographic predictors of suicidal behaviors and assessing the relationship between the spectrum of SUD and suicidal behaviors in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…En esta muestra hay un importante retraso escolar, las dificultades académicas y el abandono escolar están señalados como fuertes factores de riesgo para las conductas lesivas (2,15,19,21,22,25). Si bien el 92,5 % se encuentran escolarizados, lo cual se podría considerar como un factor protector, en cuanto a su nivel de instrucción, el 35 % de los varones tienen retraso escolar (o sea repitieron un año) y lo mismo sucede con el 52 % de las mujeres.…”
Section: Discussionunclassified
“…El vínculo entre el suicidio y los trastornos mentales, no siempre evidente (4), parecería responder a la acumulación de factores de riesgo que repercute tanto en los problemas internalizados como externalizados (7) y las situaciones individuales estresantes marcadas por la impulsividad (19). En el suicidio infantil, el Trastorno Psiquiátrico presente alrededor de un 80 %, se relaciona los trastornos del estado de ánimo, de ansiedad, del comportamiento y del consumo de sustancias (3,9).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Other major risk factors are anxiety disorders, eating disorders, alcohol and/or drug abuse, impulsive aggression, antisocial behavior, family history of suicidal behavior, and family conflict and discordance [6]. Also, two nationwide studies conducted in the United States found a significant association between suicidality and post-traumatic stress disorder, with attention-deficit/hyperactivity disorder (ADHD) increasing suicide risk in depressed adolescents by 52% [7,8].…”
mentioning
confidence: 99%